Epithelial adhesion molecules can inhibit HIV-1–specific CD8+ T-cell functions - Streeck, Hendrik; Kwon, Douglas S.; Pyo, Augustine; Flanders, Michael; Chevalier, Mathieu F.; Law, Kenneth; Jülg, Boris; Trocha, Kasper; Jolin, Jonathan S.; Anahtar, Melis N.; Lian, Jeff; Toth, Ildiko; et al. (Blood, 2011)
Under persistent antigenic stimulation, virus-specific CD8+ T cells become increasingly dysfunctional and up-regulate several inhibitory molecules such as killer lectin-like receptor G1 (KLRG1). Here, we demonstrate that HIV-1 antigen-specific T cells from subjects with chronic-progressive HIV-1 infection have significantly elevated KLRG1 expression (P < .001); show abnormal distribution of E-cadherin, the natural ligand of KLRG1, in the intestinal mucosa; and have elevated levels of systemic soluble E-cadherin (sE-cadherin) that significantly correlate with HIV-1 viral load (R = 0.7, P = .004). We furthermore demonstrate that in the presence of sE-cadherin, KLRG1hi HIV-1–specific CD8+ T cells are impaired in their ability to respond by cytokine secretion on antigenic stimulation (P = .002) and to inhibit viral replication (P = .03) in vitro. Thus, these data suggest a critical mechanism by which the disruption of the intestinal epithelium associated with HIV-1 leads to increased systemic levels of sE-cadherin, which inhibits the effector functions of KLRG1hi-expressing HIV-1–specific CD8+ T cells systemically.